Collective efficacy and natural hazards: differing roles of social cohesion and task-specific efficacy in shaping risk and coping beliefs. Issue 6 (2nd June 2020) - Babcicky, Philipp; Seebauer, Sebastian
Abstract: Previous research in non-disaster contexts has shown that the concept of collective efficacy, which is a group's sense of its ability to achieve a specific objective, assists understanding of community readiness and households' decisions to take preparedness actions. Collective efficacy expands the concept of social capital, which refers to social resources such as trust, norms and networks, by addressing how likely communities are to activate these resources for specific tasks. This paper empirically investigates the effect of three distinct collective efficacy components on risk perception, fear and self-efficacy regarding natural hazards in Austria. The three components have differing impacts on risk and coping beliefs: (1) Social cohesion decreases risk perception and fear but has no effect on self-efficacy; (2) Efficacy belief in social support increases self-efficacy; (3) Efficacy belief in citizen groups increases risk perception and fear. The combination of efficacy belief in social support and citizen groups seems to be most promising for stimulating protective action, as they together promote both risk and coping appraisal. However, overreliance on social support may have the undesirable effect of creating a false sense of safety among disaster-prone households. The findings demonstrate that collective efficacy provides a meaningful perspective from which to examine risk and coping beliefs but caution against treating it as an umbrella concept, given the differing effects of its components. Future studies are needed to investigate the impact of collective efficacy on other key explanatory factors of protective action, such as response efficacy or non-protective responses.